The The Role of Firm Size in Moderating the Relationship Between Profitability and Share Prices of Food and Beverage Companies - Taufiq Akbar (Yayasan Ilomata, 2023)
Firm size is still an interesting topic regarding its role in moderating factors that affect share prices. Therefore, the goal of this study is to determine how firm size affects the relationship of profitability, as measured by Gross Profit Margin (GPM), Operating Profit Margin (OPM), and Net Profit Margin (NPM), on share prices of manufacturing companies in the food and beverage sector from 2016 to 2019. Based on the purposive sample technique, 40 observations from 10 companies were chosen. AMOS 24 software was used to do the investigation using the structural equation modeling (SEM) method. In the initial model, it is clear from this analysis that OPM and Company Size significantly affected stock prices. At the same time, there is no significant effect of GPM and NPM on share prices. The second model demonstrates that firm size can moderate the relationship between GPM and OPM on share prices. However, this study cannot prove that firm size can moderate the effect of NPM on share prices.